PTSD and depression symptoms are associated with binge eating among US Iraq and Afghanistan veterans. (April 2015) - Hoerster, Katherine D.; Jakupcak, Matthew; Hanson, Robert; McFall, Miles; Reiber, Gayle; Hall, Katherine S.; Nelson, Karin M.
Abstract: Objective: US Iraq and Afghanistan Veterans with post-traumatic stress disorder (PTSD) and depression are at increased risk for obesity. Understanding the contribution of health behaviors to this relationship will enhance efforts to prevent and reduce obesity. Therefore, we examined the association of PTSD and depression symptoms with binge eating, a risk factor for obesity, among Iraq/Afghanistan Veterans. Method: Iraq/Afghanistan Veterans were assessed at intake to the VA Puget Sound Healthcare System-Seattle post-deployment clinic (May 2004–January 2007). The Patient Health Questionnaire was used to measure depression and binge eating symptoms, and the PTSD Checklist-Military Version assessed PTSD symptoms. Results: The majority of the sample (N = 332) was male (91.5%) and Caucasian (72.6%), with an average age of 31.1 (SD = 8.5) years; 16.3% met depression screening criteria, 37.8% met PTSD screening criteria, and 8.4% met binge eating screening criteria. In adjusted models, those meeting depression (odds ratio (OR) = 7.53; 95% CI = 2.69, 21.04; p  < .001) and PTSD (OR = 3.37; 95% CI = 1.34, 8.46; p  = .01) screening criteria were more likely to meet binge eating screening criteria. Continuous measures of PTSD and depression symptom severity were also associated with meeting binge eating screening criteria ( p s < .05). Conclusion: PTSD and depression are common conditions among Iraq/Afghanistan Veterans. In the present study, PTSD and depression symptoms were associated with meeting binge eating screening criteria, identifying a possible pathway by which psychiatric conditions lead to disproportionate burden of overweight and obesity in this Veteran cohort. Tailored dietary behavior interventions may be needed for Iraq/Afghanistan Veterans with co-morbid obesity and psychiatric conditions. Highlights: We assess correlates of binge eating among Iraq/Afghanistan veterans. Binge eating is rare among Iraq/Afghanistan veterans. Depression and PTSD symptoms are associated with binge eating. Those with mental health and binge eating symptoms should be targeted.